If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+3)=11x+7-5x+2
We move all terms to the left:
3(2x+3)-(11x+7-5x+2)=0
We add all the numbers together, and all the variables
3(2x+3)-(6x+9)=0
We multiply parentheses
6x-(6x+9)+9=0
We get rid of parentheses
6x-6x-9+9=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 4-7x=-2x+-2 | | 4-7x=-2(x+1) | | 3x+32x-5=7(5x+8) | | 3x+32x-5=7(5x+8 | | 2=10-4y-2 | | 6=2n-8-7 | | 2*((0.125)^x)=8^(3x-1) | | 36=15+7a | | X=110+y | | 6n-16=3n+8 | | 2*((0.125)^x)=0 | | 9x+3x+4x+1x=2x-3 | | x/2.x+5=115 | | |m-4|=9 | | 4x+8=4x-1 | | 0.09w=-1.8 | | 7(2x+3)=3x-5 | | x1/2=1 | | 2.5(x+4)=25 | | x+13+4x-3+9x-22=58 | | 4m-8m=10 | | 6*x+2=3/4 | | (r/5)=6 | | 6(y-4)+7y=y+120 | | X/3.5=x/5.8+8 | | 4+w+52=2(2w+1.6) | | s+63=5s | | 2/5(x)=25 | | 4(p-5)-8=-20 | | 5a=26+18a | | 82=74.6+c | | 6(x-5=5(x+5) |